A comparative study of suturing technique of intestine between extra-mucosal single layer interrupted and continuous all layers: a single center experience - Kar, Manoranjan; Singhal, Somu; Mondal, Bismoy; Roy, Arijit (International Surgery Journal, 2021)
Background: Gastrointestinal anastomosis has been excited interest in our day to day surgical practice. We have compared efficacy, advantages, disadvantages, and complications following intestinal resection-anastomosis using extra-mucosal interrupted single layer suturing or continuous all layer suturing. Methods: This comparative study included 50 cases (either in emergency or elective undergoing bowel resection and anastomosis), comprising of 2 Groups (25 cases in each Group) between January 2019 to June 2021 at Midnapore Medical College and Hospital. Patients data, operative findings, duration of anastomosis and length of hospital stay, post-operative complications of all patients were followed till discharge. Results: Our comparative study have shown that- the mean duration for intestinal anastomosis in Group A (extra-mucosal interrupted single layer) and Group B (continuous all layers) were 21.43 minutes and 14.35 respectively. Considering duration of the anastomosis continuous all layers intestinal anastomosis appears to represent in shorter duration, anastomotic leak was noted in 3 patients (6%). Anastomotic leak was observed in 1 patient extra-mucosal interrupted single layer bowel anastomosis whereas two patients in the Group of continuous all layered bowel anastomosis had leak (p value 0.5-not significant) and the mean duration of hospital stay in the Group A and Group B were 7.32 days and 7.92 days respectively. (p value -insignificant). Conclusions: Duration required to perform a continuous all layer bowl anastomosis is lesser when compared to an extra-mucosal interrupted single layer intestinal anastomosis. There is no significant difference in complications, final outcome and duration of hospital stay between two Groups.